Investigating the antibacterial effect of German chamomile flower extract as a root canal irrigation solution against Enterococcus faecalis biofilm: An in vitro study - Yaseen, Amani S; Mahdee, Anas F; Koller, Garrit; Mohmmed, Saifalarab (Journal of Baghdad College of Dentistry, 2025)
Background: Enterococcus faecalis (E. faecalis) is a prototypical resistant bacterium in root canal infections and a leading cause of endodontic treatment failure. German chamomile (Matricaria chamomilla) flower extract has been used as a traditional medicine to treat infections. The aim of this study was to investigate the antimicrobial efficacy of chamomile extract on the removal of E. faecalis root canal biofilm. Materials and Methods: Chamomile flower extract was prepared and subjected to detailed chemical analysis. For the in vitro biofilm model, human mandibular premolars (n=48) with 18-20mm working length were used. Root canal preparation was performed using the ProTaper® Next system. Each sample was split longitudinally and reassembled within a pre-prepared silicone matrix, and a mature E. faecalis biofilm was grown for seven days. Samples were randomised into four groups (n=12 for each arm) based on the type of irrigant protocol comprising normal saline, 3% sodium hypochlorite (NaOCl), dual irrigation with 17% ethylenediaminetetraacetic acid (EDTA) and 3% NaOCl, and chamomile extract. After irrigation, residual biofilms were measured in (n=9/group) using densiometric measurements. Observational analysis of residual biofilm was performed in (n=3/group) using Scanning Electron Microscopy (SEM). Results: Phytochemical investigations showed that chamomile extract is rich in antimicrobial components such as flavonoids, polyphenolic compounds, tannins, and others. Spectrophotometry analysis showed a statistically significant difference between the normal saline group with mean optical density (OD)= 0.63044; ±0.106 and each of EDTA and NaOCl group (mean OD=0.35922; ±0.091), chamomile group (mean OD=0.37611; ±0.106) at p<0.001, and the NaOCl group (mean OD=0.46344; ±0.096) at p<0.01. No statistically significant difference between chamomile group and NaOCl and the dual EDTA and NaOCl irrigation protocol. SEM images showed removal of E. faecalis biofilm and smear layer was in the order: dual EDTA and NaOCl irrigation>chamomile extract>NaOCl. Conclusions: Chamomile flower extract has an apparent removal efficacy of E. faecalis biofilm from root canals. It may be a promising antimicrobial material to be used as a natural endodontic irrigation solution.